2016
DOI: 10.1111/inr.12344
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing suicidal ideation among Chinese patients with stomach cancer: qualitative study

Abstract: Clinical nurses, hospitals and the government should work collaboratively with each other. It is suggested that Chinese national guidelines for working with the high-risk suicide populations should be considered within a future mental health working plan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Cancer patients constitute one such high‐risk group (Ahn et al, 2015; Anderson et al, 2018; Vyssoki et al, 2015). The difficulty in coping with psychosocial and physical problems may cause cancer patients to consider the idea of suicide as an option in the curing process (Zhang et al, 2017). The suicide death rate among cancer patients is approximately 2–5 times higher than the expected rate within the general population (Ahn et al, 2015; Anderson et al, 2018; Robinson et al, 2009; Vyssoki et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Cancer patients constitute one such high‐risk group (Ahn et al, 2015; Anderson et al, 2018; Vyssoki et al, 2015). The difficulty in coping with psychosocial and physical problems may cause cancer patients to consider the idea of suicide as an option in the curing process (Zhang et al, 2017). The suicide death rate among cancer patients is approximately 2–5 times higher than the expected rate within the general population (Ahn et al, 2015; Anderson et al, 2018; Robinson et al, 2009; Vyssoki et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…12 Chinese cancer patients are often unwilling to report cancer-related emotional distress or suicidal feelings to oncology nurses, which may lead to a loss of access to timely psychological assistance. 13 Although knowing the risk factors that contribute to suicide in cancer patients, they may be limited in applicability to clinical practice, especially for some nonmodifiable risk factors (eg, cancer type, time since diagnosis, etc). 5,6 Resilience is a key protective factor for suicide prevention 14 and is defined as the process of adapting well in the face of adversity, trauma, tragedy, threats, or even significant sources of threat.…”
mentioning
confidence: 99%
“…Many Chinese cancer patients believe that cancer is a deserved punishment from Buddha for their past mistakes 12 . Chinese cancer patients are often unwilling to report cancer-related emotional distress or suicidal feelings to oncology nurses, which may lead to a loss of access to timely psychological assistance 13 …”
mentioning
confidence: 99%
“…Therefore, among elderly people with cancer, there is greater vulnerability to the desire to die due to physical and mental disorder (24) . In China (25) , a qualitative study with 32 individuals with stomach cancer found that positive coping, union and family support strategies and the desire to live are protective factors for the risk of suicide. The vision problems risk factor was reformulated so that the operational definition could scale the vision problems as a consequence of the decline of the physiological system.…”
Section: Discussionmentioning
confidence: 99%